Posttraumatic growth in adolescent survivors of earthquake, tsunami, and liquefaction in Palu Indonesia: a phenomenological study - Siti Hajar Salawali; Herni Susanti; Novy Helena Catharina Daulima; Arcellia Farosyah Putri (MDPI AG, 2020)
Exploration of posttraumatic growth (PTG) experiences in adolescent survivors of earthquakes, tsunamis, or liquefaction are needed by nurses to maximize the potential for recovery and growth of adolescents from trauma after natural disasters. The study used a qualitative method with a descriptive phenomenology approach. Data were collected through in-depth interviews with 16 adolescent survivors and were analyzed using the Colaizzi method. The results of this study have two main themes: trauma becoming the basis for realizing the meaning of life and escaping from disaster as a second chance to live better. PTG is a positive change that needs to be pursued. Escaping from disaster and realizing the meaning of life are the key points to get success in pursuing PTG to live a better life. In addition, support from mental health nurses through cognitive therapy (CT) and acceptance commitment therapy (ACT) are needed to increase the PTG.